MENGUBAH STIGMA MENJADI PELUANG PENGUATAN MOTIVASI PADA WARGA BINAAN LAPAS WANITA KEROBOKAN BALI - Ramayani Yusuf; Gunardi; Dyah Bayu Framesthi; Mira Veranita; Itto Turyandi; Wahyudi (LOKATARA SARASWATI, 2025)
This Community Service aims to provide motivation to the inmates of the Women's Prison in Kerobokan, Bali. PKM with the theme "Turning Stigma into Opportunity" strengthens the motivation of inmates to rise with more confidence in facing life after leaving the prison. This PKM method uses Community-Based Participatory Research (CBPR), where the community and academics conduct activities aimed at bringing about change or improvement in conditions, which can begin with strengthening the knowledge and awareness of former inmates to be better prepared to face the stigma that occurs in society. The activity was conducted on February 13, 2025, with the participation of 40 former inmates. The presentation began with games, followed by the delivery of material and a conclusion regarding the stigma that will be faced in society and how to turn it into an opportunity. This activity provides new insights and motivation for participants to rise and rebuild their lives after leaving the correctional facility.